Kinetics of Nitrogen Removal in an Anammox Up-Flow Anaerobic Bioreactor for Treating Petrochemical Industries Wastewater (Ammonia Plant) - Alavi, Nadali; Azadi, Roza; Jaafarzadeh, Nemat; Babaei, Ali-Akbar (Asian Journal of Chemistry, 2011)
The wastewater of a petrochemical industry was treated in an anammox high rate up-flow anaerobic bioreactor (UABR). The UABR was operated under different nitrogen loading rates (NLRs) 450 mg N/L/d to 2083 mg N/L/d and hydraulic retention time (HRT) from 24 to 6 h, in order to determine the substrate removal kinetics of the reactor. As hydraulic retention time was decreased, ammonium removal efficiency decreased from 93.7 % to 83 %, as well as total nitrogen removal efficiency decreased from 92.4 % to 83.6 %. However, nitrite removal efficiency did not change significantly indicating nitrite was the limiting nutrient. Three kinetic models including firstorder, Grau second-order and modified Stover-Kincannon, applied to determine the process kinetics of the nitrogen removal in the UABR. The experimental data showed that the kinetics of nitrogen removal by anammox process followed the Grau second-order and modified Stover- Kincannon models for predicting the performance of UABR for treating the petrochemical industrial wastewater.